Transcending Epistolary Communication: Prayer in First Thessalonians - Lang, Maria B. (New Testament studies, 2025)
Prayer is one of the basic elements of religious life and is widespread in most religions. It is the human act, verbal and non-verbal, of communicating with a transcendent being (in the broadest sense). In comparison to its communicative function, the written form of prayer is secondary. This study differentiates between prayer as act, prayer as text and prayer as subject, understood as any reference to or statement made about prayer. In First Thessalonians, as in contemporary letters, prayer as subject can be found in a variety of ways. An especially remarkable feature is the prayer texts and acts of prayer (although these are not numerous and mostly short), which imply a change of addressee within the communicative situation of the letter. Against the background of ancient letters and epistolary conventions of the time, this article examines the characteristics and the specific function of prayer (as text, act and subject) in First Thessalonians. It argues that the Christian message shapes and multiplies the references to prayer, also integrating short texts and acts of prayer which transcend the epistolary communication, deepening not only the relationship between Paul, Silvanus, and Timothy and the Thessalonians but also their relationship to God and in God.